2018
DOI: 10.17509/mimbar-sd.v5i3.14492
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Communication Politeness: A Survey of Prospective Primary School Teacher Students

Abstract: The presence of social media into daily life has had a positive and negative impact on communicating manners. This impact also occurs in the educational environment or on campus. This paper aims to analyze student politeness in communicating through social media. The study was conducted by providing a survey of 147 students (ages between 19-24 years). The results of the study prove that communication through social media has an impact on students to be more willing to communicate with anyone. However, politene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Turkey has the same issue which was discovered through a survey of recently enrolled college students. Their use of digital devices for literary activities also requires assistance and support (Julia, Kurnia, & Sudin, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Turkey has the same issue which was discovered through a survey of recently enrolled college students. Their use of digital devices for literary activities also requires assistance and support (Julia, Kurnia, & Sudin, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…They can be extremely helpful because of their instantaneous internet access and ability to store data in multiple media formats which can be used with almost no limitations. They can even assist teachers or students in evaluating their progress in learning (Bayanova et al, 2019;Julia et al, 2018). In fact, gadgets can encourage students to learn important knowledge but they have not used their devices to their full potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of technology, a new generation of students spend a lot of time in front of the computer in their academic and social lives and use the internet and technology extensively. Today's students are closely related to technology, and most of them are technology literate (Julia et al, 2018). For this reason, online platforms should be used for students with an interesting content presentation, easy to use, where they can interact with the content and allow them to observe (Ricci et al, 2013).…”
Section: Problem Statementmentioning
confidence: 99%
“…Thus, she has suggested that online communication should manifest appropriate attitudes, offer the teacher's response on time to the students' requests, and respect the confidentiality of the communication content (Mâță, 2022). Similarly, Julia, Kurnia, and Sudin (2018) have shown that communication between students and their peers and between students and their lecturers through social media decreased politeness and tended to ignore the ethics of communication. This is an interesting finding because Gervasio and Humphrey (2019) have found the opposite.…”
Section: Introductionmentioning
confidence: 99%